Ichthyosis Fetalis - Rusdidjas Rusdidjas; Helena Siregar; Sjarikat Tarigan (Paediatrica Indonesiana, 1978)
A severe variety of ichthyosis fetalis or Harlequin fetus is reported with a brief review of the literature. It seemed that our case, Tadjuddin's (Jakarta), and Wong Hock Boon's (Singapore) assure us that the Harlequin fetus can also be seen in the tropics and in all traces where the ichthyosis gene is present.